(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article analyzes the health risks associated with the practice of rapid weight loss among athletes. Based on scientific studies, it is shown that a sharp reduction in body weight over a short period of time through prolonged fasting, dehydration, or the use of diuretics and thermogenic substances has a negative impact on the athlete’s overall condition, cardiovascular system, electrolyte balance, and psychological state. It is also noted that rapid weight loss may have not a positive but a negative effect on athletic performance.